2019
DOI: 10.3747/pdi.2018.00125
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intravenous Iron – Cosmofer and Monofer Therapy in Peritoneal Dialysis and Non-Dialysis-Dependent Chronic Kidney Disease Patients

Abstract: Safety of parenteral iron therapy is critical and has been demonstrated in several studies, but concerns persist on safety. We performed a retrospective single-center study investigating the safety and efficacy of parenteral iron administration using 2 iron preparations-Monofer and Cosmofer (Pharmacosmos A/S, Holbaek, Denmark)-in patients with chronic kidney disease (CKD), on peritoneal dialysis (PD) and non-dialysis. A database of CKD patients receiving intravenous (IV) iron was analyzed. Side effects were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
2
11
2
Order By: Relevance
“…Data from clinical trials have confirmed the good efficacy and safety profile of IIM in patients with CKD [8,[16][17][18][19]. In addition, observational studies in CKD conducted in Germany [20], Scandinavia [21], and the UK [22], have demonstrated that IIM is well tolerated and effective in real-world settings.…”
Section: Introductionmentioning
confidence: 86%
“…Data from clinical trials have confirmed the good efficacy and safety profile of IIM in patients with CKD [8,[16][17][18][19]. In addition, observational studies in CKD conducted in Germany [20], Scandinavia [21], and the UK [22], have demonstrated that IIM is well tolerated and effective in real-world settings.…”
Section: Introductionmentioning
confidence: 86%
“…In patients with NDD‐CKD, IV iron has been shown to rapidly correct anemia and reduce need for ESAs relative to oral iron without evidence of renal toxicity, cardiovascular, or infectious events . Rates of acute infusion‐related hypersensitivity reactions are low with IV iron use in NDD‐ and PD‐CKD patients and the safety of short‐term IV iron is established by multiple trials . A trial of oral iron may however be considered in NDD‐CKD patients based on the severity of their anemia, previous response to oral iron, venous access, and cost considerations .…”
Section: Anemia In Chronic Kidney Diseasementioning
confidence: 99%
“…66 Rates of acute infusion-related hypersensitivity reactions are low with IV iron use in NDD-and PD-CKD patients and the safety of short-term IV iron is established by multiple trials. [67][68][69] A trial of oral iron may however be considered in NDD-CKD patients based on the severity of their anemia, previous response to oral iron, venous access, and cost considerations. 61 Use of ESAs increases utilization of iron stores for hematopoiesis; they should only be used after functional or absolute iron deficiency has been corrected.…”
Section: Anemia In Chroni C K Idne Y Dise a Sementioning
confidence: 99%
“…The frequencies vary greatly, depending on the type of study performed. Brief descriptions of the studies in Table II 4,5,21,[37][38][39][40][41][42][43][44] follow in the paragraphs below, according to the type of study. Retrospective studies based on figures reported to centralized databases Fletes et al 4 analysed data from the clinical variance reports of Fresenius Medical Care North America (which distributes dialysis equipment).…”
Section: Frequency Of Severe Allergic Reactions To IV Ironmentioning
confidence: 99%
“…Sivakumar et al 43 retrospectively reviewed charts of patients on various types of dialysis, for various ADEs. Only one patient developed a suspected anaphylactic reaction ('collapse') requiring active medical intervention for recovery.…”
Section: Retrospective Reports Based On Primary Data Of Patients Treated With IV Ironmentioning
confidence: 99%